2016
DOI: 10.1016/j.jom.2016.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Conducting and publishing design science research

Abstract: a b s t r a c tThe new Design Science department at the Journal of Operations Management invites submissions using a design science research strategy for operations management (OM) issues. The objective of this strategy is to develop knowledge that can be used in a direct and specific way to design and implement actions, processes or systems aimed at achieving desired outcomes. This knowledge is developed by engaging with real-life OM problems or opportunities. Manuscripts submitted to this department will be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
99
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 231 publications
(127 citation statements)
references
References 25 publications
1
99
0
Order By: Relevance
“…DSR aims at developing a solution that solves a practical problem and provides contributions to the associated theoretical knowledge [46]. The innovative solution, called artefact, is usually developed in cycles of evaluation and redesign [47]. The artefact may include constructs, models, methods and instantiations [48].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…DSR aims at developing a solution that solves a practical problem and provides contributions to the associated theoretical knowledge [46]. The innovative solution, called artefact, is usually developed in cycles of evaluation and redesign [47]. The artefact may include constructs, models, methods and instantiations [48].…”
Section: Methodsmentioning
confidence: 99%
“…The research was divided into four stages, following the steps suggested for DSR [47]: (a) define the problem; (b) plan the intervention; (c) implement the intervention and (d) evaluate it. As shown in Figure 2, the development of the BIM protocol was highly iterative, as is typical of DSR projects.…”
mentioning
confidence: 99%
“…Research on such marketing communication and branding instruments designed by humans, such as in advertising research, is "a design science, aiming to generate a body of knowledge on how to create, improve, orchestrate, and manage specific types of marketing instruments" (Henseler, 2017a, p. 178). Design science research itself is a research strategy that aims to create knowledge that can be used to design and implement actions, processes or systems to achieve desired outcomes in practice (van Aken et al, 2016). Based on a process comprising different steps, such as problem identification and exploration, the search for initial solutions, and the own development of a solution (Holmström et al, 2009;G.…”
Section: Rq2: How Do Brand Worlds Work In Industrial Marketing?mentioning
confidence: 99%
“…Answering these questions with respect to these carefully designed physical artifacts can be seen as the last, crucial step of the design science research process: testing and evaluating whether a design or artifact actually 'works', i.e. whether it is effective in solving a problem (van Aken, Chandrasekaran, & Halman, 2016). Furthermore, understanding 'how' it works subsequently allows for further improvements of the design and its implementation (Holmström, Ketokivi, & Hameri, 2009;G.…”
mentioning
confidence: 99%
See 1 more Smart Citation